Diffuse 18F-FDG Muscle Uptake in Trichinella spiralis Infection. (January 2016) - Deroose, Christophe M.; Van Weehaeghe, Donatienne; Tousseyn, Thomas; Van Rompuy, Anne-Sophie; Vanderschueren, Steven; Blockmans, Daniel; Gheysens, Olivier
Abstract : Abstract: Two patients were referred to our emergency department with myalgia, fever, general malaise, eosinophilia, and elevated serum levels of creatine kinase and troponin T. 18 F-FDG PET/CT scan was performed showing a diffuse and homogenous moderately elevated glucose uptake in all muscle groups. Trichinella spiralis infection was confirmed by a muscle biopsy and detection of trichinella antibodies. The muscle biopsy was taken in the left quadriceps because of equal involvement of the skeletal muscles. The differential diagnosis of diffuse 18 F-FDG muscle uptake should include trichinella infection, in particular, in the presence of infectious symptoms, eosinophilia, and biochemical signs of muscle damage.